Bonding of permanent tooth fracture without pulp exposure: a case report - Cavalli, Marcelo Arthur; Oliveira, Bill Okuma; Nuernberger, Paulo Vitor Freitas; Cristófaro, Márcio; Cadioli, Isabela Capparelli; Wanderley, Márcia Turolla (Clinical and Laboratorial Research in Dentistry, 2014)
Dental trauma is a serious oral health problem which is prevalent in the population, especially in children with protrusion of the maxillary incisors. Enamel and dentin combined fractures are the most prevalent among permanent tooth fractures. Bonding of the fractured tooth is described as an alternative therapy for fractured teeth; however, it involves factors that infl uence treatment success: the existence of the tooth remainder, the time elapsed between trauma and treatment, the involvement of enamel, dentin and pulp chamber, and the bonding technique. This study was conducted in the undergraduate clinic of the Discipline of Pediatric Dentistry, School of Dentistry, University of Sao Paulo, and describes a simplifi ed bonding technique applied to a combined enamel and dentin fracture of a right maxillary central incisor, without pulp involvement, in a nine-year-old male child. The importance of patient management, proper indication, therapy limitations, prognosis and follow-up are also discussed in this study.